Analysis of the concrete shrinkage effects on the real behavior of the spatial concrete and reinforced concrete structures using the thermal analogy. Issue 4 (6th December 2019) - Džolan, Ante; Kožul, Mladen; Harapin, Alen; Ćubela, Dragan
Abstract : Purpose: This paper aims to present an approach for the numerical simulation of concrete shrinkage. First, some physical mechanisms of shrinkage are described and then the developed numerical model for the analysis of shrinkage of spatial three-dimensional structures using thermal analogy is presented. Results of the real behavior of structures because of concrete shrinkage using the developed numerical model are compared with the experimental and it is clearly shown that the developed numerical model is an efficient tool in predicting the time-dependent behavior of all concrete structures. Design/methodology/approach: In this paper, Fib Model Code 2010 to predict shrinkage deformation of concrete is used, and it was incorporated in the three-dimensional numerical model using the thermal analogy. Mentioned three-dimensional numerical model uses the modified Rankine material law to describe concrete behavior in tension and modified Mohr-Coulomb material law to describe concrete behavior in compression. The developed three-dimensional numerical model successfully analyzes the behavior of reinforced and/or prestressed concrete structures including time-dependent deformations of concrete as well. Findings: Results are shown in this paper clearly demonstrate the reliability of the developed numerical model in predicting the shrinkage strain, as well as its impact on concrete and reinforced concrete structures. The results obtained using the developed numerical model are in better agreement with the experimental results, than the results obtained using the numerical models from literature that also use the Fib Model Code 2010 to predict the shrinkage strain. So, it can be concluded that for a real simulation of concrete structures, alongside the model for predicting the shrinkage strain, the models for concrete behavior in tension and compression have a very important role. Originality/value: Results of the developed three-dimensional numerical model were compared with experimental results from literature and with theoretical foundations, and it can be talked that this numerical model presents a good tool for analysis of reinforced and prestressed concrete structures including shrinkage deformation of concrete. Results obtained using the developed three-dimensional numerical model are better agreed with experimental than results of other numerical model from literature.